ORIGIN AND PARAGENETIC ASSOCIATIONS OF CHEMOGENIC HIGH-AL DEPOSITS IN THE KIKHPINYCH LONG-LIVED VOLCANIC CENTER, KAMCHATKA - Kardanova O.F.; Karpov G.A. (My University, 2000)
Chemogenic high-Al deposits (protobauxites) were studied in the geothermal fields of Kikhpinych Volcano. Conditions of their deposition, mineralogy, and paragenetic associations are discussed. The main factors that favored the emplacement of aluminous deposits under nival climate conditions are believed to be (1) the mixing of acid (pH < 3.5) water containing Al+3 ions from low-discharge streams with more alkaline water (pH > 7) from larger streams, (2) high Ca+2 and Mg +2 ion concentrations in one of the streams, and (3) a specific ratio between the hydroxyl-ion and Al ion concentrations and the sulfate-ion in the solution. The fresh sediments are X-ray amorphous, but after being stored for 5-7 years, the samples showed gibbsite, goethite, and other minerals developed in them.